Quantum Simulation of Complex Molecular Dynamics Using Quantum Annealing - Haruka Sato; Ren Suzuki; Miku Fujita (Yayasan Adra Karima Hubbi, 2024)
Quantum simulation of complex molecular dynamics using quantum annealing has great potential to solve complex and complex molecular simulation problems. Quantum annealing, which optimizes the search for solutions in the energy space by utilizing quantum phenomena, offers advantages in speeding up the simulation process compared to classical methods. This study aims to explore the use of quantum annealing in complex molecular simulations, focusing on its effectiveness in finding molecular configurations with minimum energy. The method used involves simulation experiments using quantum annealing hardware and comparing the results with classical simulations. The results show that quantum annealing can improve computational time efficiency and produce more accurate solutions on large molecules with complex interactions. Although there are some limitations of current quantum hardware, the results of this study show the great potential for the use of quantum annealing in molecular dynamics simulations. Further research needs to be focused on improving quantum hardware and developing more advanced algorithms to support more complex molecular simulations.